A SUSTAINABILITY AWARENESS PROFILE OF SMK STUDENTS THROUGH ESD-ORIENTED PROJECT-BASED LEARNING: PROFIL SUSTAINABILITY AWARENESS SISWA SMK MELALUI PEMBELAJARAN BERBASIS PROYEK BERORIENTASI ESD - DYAH SISKAWATI (Jurnal Kualita Pendidikan, 2023)
Education in Indonesia realizes sustainable development through the implementation of ESD in Vocational High Schools (SMK). Although ESD has been attempted in Indonesia, especially at the vocational world education level, based on the results of observations in the field, it turns out that the learning in the classroom is still not fully directed towards Education Sustainable Development, even though it can actually be integrated properly, for example in learning the Sciences Project. ESD is very important in building students' mindsets and lifestyles in the present and in the future, so this research was conducted to obtain more concrete information about students' sustainability awareness profiles through the integration of ESD in the IPAS Project learning, which is considered can support student awareness (sustainability awareness). The researcher carried out a quantitative research approach using the One shoot case study method through a survey with a random sample of 482 students in 2 SMKs in Semarang Regency online by means of an analytical descriptive method. The instrument used is a questionnaire with a Likert scale (without a neutral choice) which is given after the learning process. Through this research, data was obtained that Continuity Awareness (Sustainability Awareness) with emotional and behavioral and attitude categories included the "often done" criteria but the practice awareness category included the "rarely done" criteria. Based on the results of this study, it is suggested for SMK teachers to increase students' awareness of environmental issues and sustainability through the integration of ESD concepts in all subjects as well as hands-on programs such as clean-up activities and recycling arts. Involving the local community as part of the learning process and providing assistance by teachers who are competent in the field of ESD can also help increase awareness of sustainability in SMK students.